Properties of particleboard manufactured from commonly utilized Malaysian bamboo (Gigantochloa scortechinii) - Kasim, Jamaludin; Ahmad, Abd. Jalil; Harun, Jalaludin; Ashaari, Zaidon; Mohmod, Abdul Latif; Mohd Yusoff, Mohd Nor (Universiti Putra Malaysia Press, 2001)
Buluh semantan (Gigantochloa scortechinii), one of the most widespread bamboo species in Peninsular Malaysia was investigated for its suitability as a raw material for particleboard production. A total of 120 bamboo culms from three different age group (1-,2 and 3-y-old) were harvested from managed bamboo clumps in FRIM. The bamboo particles produced from the flaking process were used in the making of single- and three-layer urea formaldehyde particle boards. The particleboard produced were then tested for their mechanical properties and dimensional stability according to British Standard Methods. The result showed that age, resin content and board density significantly affected the single-layer particleboard properties, while for three-layer particleboard the effect of age, core particle size and wax addition on the board properties were also found to be significant. Irrespective of bamboo age, particles of Gigantochloa scortechinii are suitable for the manufacture of urea formaldehyde particle boards.